A zinc-containing metal soap heat stabilizer for PVC, and a preparation method and application thereof
Patent Information
- Application Number
- CN202311507655.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-13
AI Technical Summary
[0003]1.仅有热稳定效果,对PVC的拉伸强度、冲击强度、抗蠕变性能和耐磨等没有大的改善效果
[0058](1)本发明的稳定剂与PVC相溶性更好,热稳定效果更好,加工成型冷却后,接枝到PVC链上的稳定剂上的呋喃基团就会和双马来酰亚胺加成形成网状交联,起到增加机械强度,一定增韧效果,稳定剂不易析出,大大减轻热稳定剂的压析和喷霜现象。
Smart Images

Figure CN117551304B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer modification technology, specifically to a zinc-containing metal soap heat stabilizer for PVC, its preparation method, and its application. Background Technology
[0002] Polyvinyl chloride (PVC) is one of the five major general-purpose plastics, second only to polyethylene (PE) in production volume. Due to its low price, its products have a wide range of applications. However, PVC has poor thermal stability, requiring the addition of appropriate heat stabilizers during processing to inhibit thermal degradation. Furthermore, PVC's tensile strength, impact strength, creep resistance, and abrasion resistance are not particularly good, necessitating modification to improve its performance. For economic and environmental reasons, PVC heat stabilizers are currently mainly metal soaps. These metal soap heat stabilizers are primarily zinc fatty acid soaps, barium soaps, and calcium soaps, which have the following disadvantages:
[0003] 1. It only has a heat stabilizing effect and does not significantly improve the tensile strength, impact strength, creep resistance, and wear resistance of PVC.
[0004] 2. It is not compatible with PVC resin and is distributed in clumps in PVC. Only the metal soaps on the surface of the clumps play a stabilizing role, resulting in poor stabilization effect.
[0005] 3. Due to its poor compatibility with PVC resin and its small molecular weight, the product may deposit on the equipment during production, causing "pressure precipitation". During use and storage, the stabilizer may seep out on the product surface in the form of blooming, affecting the product's appearance.
[0006] In its early research, CN112010779A disclosed a modified metal soap heat stabilizer, its preparation method, and its application. The method involves mixing diisocyanate and a monohydric alcohol to obtain a modified intermediate. Then, ricinoleic acid metal soap or hydrogenated ricinoleic acid metal soap is melted and reacted with the modified intermediate to obtain modified ricinoleic acid metal soap heat stabilizer and modified hydrogenated ricinoleic acid metal soap heat stabilizer. These methods can improve the compatibility and dispersion effect on PVC. However, this invention cannot improve the mechanical strength of PVC materials, and irreversible cross-linking occurs under high-temperature conditions, leading to poor reprocessability of the PVC material. Therefore, further improvements are needed.
[0007] CN103571108A discloses an environmentally friendly composite stabilizer for PVC based on graphene oxide salt, comprising 50-90 parts by weight of a main stabilizer and 10-50 parts by weight of an auxiliary stabilizer. The main stabilizer is a complex of graphene oxide salt and metal soap salt, which can be prepared by reacting graphene oxide with an excess of inorganic alkali to obtain solid graphene oxide salt, and then compounding it with metal soap salt; or by reacting graphene oxide with an inorganic alkali, controlling the excess inorganic alkali to be 20%-50%, and then adding fatty acids to the reaction solution to neutralize the unreacted inorganic alkali. This composite stabilizer has good thermal stability and also exhibits good reinforcing and toughening effects on PVC resin. However, the preparation method of this stabilizer is cumbersome and complex, and the cost of raw materials such as graphene oxide is relatively high, making it difficult to promote its application in industrial production. Summary of the Invention
[0008] This invention addresses the shortcomings of existing metal soap-based PVC stabilizers by providing a heat stabilizer that can reversibly crosslink with polyvinyl chloride. By modifying the metal soap stabilizer molecules, it not only improves compatibility with PVC and effectively reduces or eliminates blooming and segregation phenomena, exhibiting better heat stability, but also improves the tensile strength, impact strength, and other mechanical properties of PVC.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0010] A zinc-containing metal soap heat stabilizer for PVC, comprising the following raw material components based on a total mass of 100 parts:
[0011] 10-85 parts of primary stabilizer;
[0012] Synergistic stabilizer 15-90 parts;
[0013] The main stabilizer has the structure shown in Formula I:
[0014]
[0015] The synergistic stabilizer has the structure shown in Formula II:
[0016]
[0017] Wherein, R1 is CH2CH2 or CH=CH, R2 is a diisocyanate residue, R3 is NH or O, M is any one or more of alkaline earth metal elements and rare earth metal elements; n = 2, 3 or 4.
[0018] This invention utilizes a furan-maleimide reversible crosslinking system and urethane / urea synergistic modification of ricinoleic acid soap, allowing it to exist as a dicarboxylic acid soap at lower temperatures and dissociate into a monocarboxylic acid soap at PVC processing temperatures, exhibiting reversible crosslinking properties (e.g., the reaction mechanism of the main stabilizer).Figure 1 Because PVC molecules contain numerous allyl chloride and tert-butyl chloride, these chlorides are considered unstable. At processing temperatures (150–200°C), they accelerate dechlorination to form hydrogen chloride, leading to the formation of even more allyl chloride. Hydrogen chloride then catalyzes PVC dechlorination, resulting in a chain reaction and rapid decomposition. The main function of the stabilizer in this invention is to replace the unstable tert-butyl chloride and allyl chloride to form zinc chloride. The stabilizer's acyl groups are then grafted onto the PVC molecular chain, reducing the amount of unstable chloride during the reaction and preventing the formation of hydrogen chloride that could lead to subsequent PVC decomposition. When the PVC is processed, molded, and cooled, the furan groups on the stabilizer grafted onto the PVC chain react with bismaleimide to form a network crosslink, significantly increasing the mechanical strength of the PVC. This also improves compatibility with the PVC matrix and provides a certain toughening effect, ensuring the stabilizer does not easily precipitate and preventing pressure precipitation and blooming (e.g., the reaction mechanism of the main stabilizer is as follows). Figure 2 ).
[0019] The alkaline earth metal element includes one or more of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); barium or calcium is preferred considering cost and effectiveness;
[0020] The rare earth metal elements include one or more of the following: lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and yttrium (Y). For castor oil acid rare earth soap, the rare earth elements are predominantly in the trivalent state. Lanthanum and cerium are preferred considering the availability of the elements.
[0021] The diisocyanate residues are derived from one or more of MDI (4,4'-diphenylmethane diisocyanate), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), and isophorone diisocyanate (IPDI). MDI and TDI are preferred considering material availability and ease of reaction.
[0022] The preparation method of the primary stabilizer or synergistic stabilizer includes the following steps:
[0023] Step 1: Reaction of castor oil soap with diisocyanate yields intermediate A;
[0024] Step 2: Intermediate A is reacted with furanol (furfuryl alcohol) or furanylmethylamine (furfurylamine) to generate intermediate B; preferably, it is reacted with furanylmethylamine.
[0025] Step 3: React intermediate B with bismaleimide to obtain the main stabilizer or synergistic stabilizer;
[0026]
[0027] When preparing the main stabilizer, the ricinoleic acid soap in step 1 is zinc ricinoleate or hydrogenated zinc ricinoleate; X in the structural formulas of intermediates A and B is Zn;
[0028] When preparing the synergistic stabilizer, in step 1, the ricinoleic acid soap is any one of ricinoleic acid alkaline earth soap, ricinoleic acid rare earth soap, hydrogenated ricinoleic acid alkaline earth soap, and hydrogenated ricinoleic acid rare earth soap; in the structural formulas of intermediate A and intermediate B, X is M, and M is any one or more of alkaline earth metal elements and rare earth metal elements.
[0029] This invention also provides a method for preparing the zinc-containing metal soap heat stabilizer for PVC, comprising the steps of:
[0030] Step 1: Reaction of castor oil soap with diisocyanate yields intermediate A;
[0031] Step 2: Intermediate A is reacted with furanol or furanylmethylamine to generate intermediate B;
[0032] Step 3: React intermediate B with bismaleimide to obtain the main stabilizer or synergistic stabilizer;
[0033] Step 4: Weigh the main stabilizer and synergistic stabilizer according to the proportions specified in claim 1 to prepare the zinc-containing metal soap heat stabilizer;
[0034]
[0035] When preparing the primary stabilizer, the ricinoleic acid soap in step 1 is zinc ricinoleate or hydrogenated zinc ricinoleate; X in the structural formulas of intermediates A and B is Zn; the reaction formula can be represented as:
[0036]
[0037] When preparing the synergistic stabilizer, in step 1, the ricinoleic acid soap is any one of ricinoleic acid alkaline earth soap, ricinoleic acid rare earth soap, hydrogenated ricinoleic acid alkaline earth soap, and hydrogenated ricinoleic acid rare earth soap; in the structural formulas of intermediate A and intermediate B, X is M, and M is any one or more of alkaline earth metal elements and rare earth metal elements.
[0038] More specifically, the preparation method includes the following steps:
[0039] Step 1: Heat the castor oil soap until it melts, remove the moisture by vacuuming, add solvent to dissolve it, and then add diisocyanate and react at 55-80℃ for 0.5-6 hours. If the reaction temperature of isocyanate and hydroxyl groups exceeds 120℃, the side reactions will intensify, the product composition will become more complex, and the product color will be darker. Generally, the reaction temperature is controlled below 80℃, preferably controlled at 55-65℃.
[0040] Step 2: Add furanol or furanylmethylamine to the reaction mixture from Step 1, and react at 55-80°C for 2-6 hours.
[0041] Step 3: Add bismaleimide to the reaction mixture from Step 2, react at 55-80°C for 4-12 hours, remove the solvent from the reaction solution and dry to obtain the main stabilizer or synergistic stabilizer.
[0042] Step 4: Weigh the main stabilizer and synergistic stabilizer according to the proportions specified in claim 1 to prepare the zinc-containing metal soap heat stabilizer.
[0043] Since all ricinoleic acid soaps have melting points above 60°C, and barium ricinoleate has a melting point exceeding 120°C, the product quality and color cannot be satisfied when reacting with isocyanate at the melting temperature. Therefore, this invention adopts a solvent method, first dissolving the ricinoleic acid soap in a solution, and then reacting it with diisocyanate.
[0044] The molar ratio of the diisocyanate to the hydroxyl group of the ricinoleic acid soap is 0.8-1.2:1;
[0045] The molar ratio of furanol or furanylmethylamine to diisocyanate is 0.8-1.2:1;
[0046] The molar ratio of the bismaleimide to furanol or furanylmethylamine is 0.45-0.55:1;
[0047] To further reduce the occurrence of side reactions, it is preferable that each reactant is added in the reaction stoichiometric ratio, with the molar ratio of hydroxyl groups of diisocyanate to ricinoleic acid soap being 1:1; the molar ratio of furanol or furan methylamine to diisocyanate being 1:1; and the molar ratio of bismaleimide to furanol or furan methylamine being 0.5:1.
[0048] The reaction processes in steps 1-3 are all carried out under the protection of an inert gas, which includes one or more of nitrogen and argon.
[0049] The solvent includes one or more of toluene, xylene, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), and diethylformamide (DEF). Toluene is preferred for the initial addition of solvent, and subsequent additions may be made, with DMF being the preferred solvent for subsequent additions.
[0050] Isocyanates react faster in nonpolar solvents such as toluene or xylene than in polar solvents such as DMF. The solubility of intermediates A and B and the final product decreases in toluene or xylene. Therefore, it is necessary to add polar solvents with good solubility, such as DMF, to ensure the homogeneity of the reaction system and prevent product precipitation.
[0051] Because water reacts with isocyanates to produce a series of insoluble and harmful byproducts, preferably, in step 1, the ricinoleic acid soap is heated to melt and then vacuum-sealed to remove the adsorbed water. When the temperature drops to around 100°C (higher temperatures result in greater solvent evaporation, while lower temperatures slow down the dissolution rate), a solvent is added to dissolve the ricinoleic acid soap. After complete dissolution, the temperature is lowered to below 80°C, and then diisocyanate is added to carry out the reaction. Below 80°C, there are fewer side reactions. The reaction rate of ricinoleic acid soap with isocyanate in non-polar solvents such as toluene or xylene is much faster than in polar solvents (DMF, etc.), which can shorten the reaction time.
[0052] Preferably, in step 2 or step 3, a reaction solvent may be added.
[0053] This invention also provides a highly stable PVC material, comprising, by weight, 100 parts of PVC matrix and 1-10 parts of the zinc-containing metal soap heat stabilizer. The stabilizer of this invention is a heat stabilizer that enables reversible crosslinking of polyvinyl chloride and exhibits good compatibility. By incorporating Diels-Alder reversible crosslinking groups and urethane esters into the metal soap stabilizer molecules and modifying them, the resulting modified heat stabilizer enables crosslinking of PVC molecular chains, increasing the mechanical strength of PVC and exhibiting good compatibility with PVC. It also improves PVC's dispersibility in PVC, enhances heat stabilization, reduces or eliminates blooming and segregation phenomena, and improves the tensile strength, impact strength, creep resistance, and abrasion resistance of PVC through crosslinking.
[0054] Preferably, the highly stable PVC material comprises, by weight, raw materials:
[0055]
[0056] This invention also provides a method for preparing the aforementioned highly stable PVC material, comprising the steps of: mechanically blending all raw materials and melt-extruding to obtain the PVC material. The melt-extrusion temperature is 150–200°C.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The stabilizer of the present invention has better compatibility with PVC and better heat stabilization effect. After processing and molding and cooling, the furan group on the stabilizer grafted onto the PVC chain will add with bismaleimide to form a network crosslink, which increases mechanical strength and has a certain toughening effect. The stabilizer is not easy to precipitate, which greatly reduces the pressure precipitation and blooming phenomenon of heat stabilizer.
[0059] (2) The stabilizer designed in this invention can generate cross-links between PVC molecules at low temperatures (below 100℃) to improve the mechanical strength of PVC materials. At processing temperatures above 150℃, the cross-links between PVC molecules will break, without affecting secondary processing, thus achieving the effect of reversible cross-linking.
[0060] (3) The stabilizer preparation method of the present invention is simple and the reaction conditions are mild, and it can be directly industrialized and promoted. Attached Figure Description
[0061] Figure 1 This is a diagram illustrating the reversible crosslinking reaction mechanism of the main stabilizer in this invention.
[0062] Figure 2 This is a diagram illustrating the reversible crosslinking reaction mechanism between the main stabilizer and the PVC matrix in this invention. Detailed Implementation
[0063] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Modifications or equivalent substitutions made by those skilled in the art based on their understanding of the technical solutions of this invention, without departing from the spirit and scope of the invention, should be covered within the protection scope of this invention.
[0064] The raw materials used in the following specific embodiments were all purchased from the market. The preparation process of the main stabilizer or synergistic stabilizer of the invention is as follows:
[0065] Raw materials: Polyurethane-grade solvents toluene and DMF, ricinoleic acid soap / hydrogenated ricinoleic acid soap, furfurylamine, diisocyanate, and bismaleimide, all purchased commercially. Equipment includes a 50-liter stainless steel reactor with a nitrogen bottom-blowing pipe, reflux condenser, and vacuum distillation unit, a vacuum pump, and a crusher.
[0066] Before production, the ricinoleic acid soap must be tested to determine the hydroxyl value of the product or obtain the accurate hydroxyl value of zinc ricinoleate from the raw material manufacturer.
[0067] Step 1: Open the valve of the nitrogen blow-off pipe at the bottom of the reactor to expel the air, then turn off the nitrogen and add ricinoleic acid soap. Heat to 150°C, turn on the vacuum pump, and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture.
[0068] Step 2: Turn off the vacuum pump and simultaneously open the valve of the nitrogen purging pipe at the bottom of the reactor. Open the gas valve to release the internal pressure. Once the reactor is filled with nitrogen, close the bottom purging valve and purge with nitrogen. When the temperature drops below 100℃, add an appropriate amount of toluene and stir until the ricinoleic acid soap is completely dissolved. Add diisocyanate with the same molar number of hydroxyl groups as the ricinoleic acid soap, control the temperature at 60-80℃, and react for 0.5-6 hours.
[0069] Step 3: Cool the reaction solution to 60°C, add a small amount of DMF solvent, and keep the reaction at 60°C for 2-6 hours with the same molar amount of furfurylamine as diisocyanate. Then add half a molar amount of bismaleimide as furfurylamine and keep the reaction at 55-80°C for 4-12 hours.
[0070] Step 4: Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solvent can be reused after recovery. The solids at the bottom of the vessel are cooled and crushed to obtain DA modified castor oil soap stabilizer. For small samples, the reaction solution can also be placed in an evaporating dish and the solvent removed in a ventilated low-temperature oven.
[0071] Example 1
[0072] The hydroxyl content of zinc ricinoleate raw material was accurately measured, and the hydroxyl value was 161.25 mg kOH / g.
[0073] (1) Purge nitrogen into the reaction vessel to remove air. Take 5 kg of zinc ricinoleate (containing about 14.394 mol of hydroxyl groups) and heat it to 150°C. Turn off the nitrogen and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool it to 70-80°C under a nitrogen atmosphere. Add 10 kg of polyurethane-grade solvent toluene and start stirring until the zinc ricinoleate is completely dissolved. Control the temperature at 75°C and add 2.51 kg (about 14.4 mol) of TDI-100 dropwise into the zinc ricinoleate solution. Maintain the reaction at 75°C for 1.5 hours.
[0074] (2) Cool to 60°C, add 1.5 kg of DMF solvent, and then add 1.397 kg of furfurylamine (14.4 mol) and react for 3 hours.
[0075] (3) Add 2.578 kg (7.2 mol) of bismaleimide and keep warm at 60°C for 12 hours.
[0076] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA modified zinc ricinoleate soap stabilizer.
[0077] Example 2
[0078] The hydroxyl content of the calcium castor oil raw material was accurately measured, and the hydroxyl value was 167.675 mg kOH / g.
[0079] (1) Purge nitrogen into the reaction vessel to remove air. Take 5 kg of calcium ricinoleate (containing about 14.961 moles of hydroxyl groups) and heat it to 150°C. Turn off the nitrogen and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool it to 70-80°C under a nitrogen atmosphere. Add 10 kg of polyurethane-grade solvent toluene and start stirring until the calcium ricinoleate is completely dissolved. Control the temperature at 75°C and add 2.61 kg (about 15 moles) of TDI-100 dropwise into the calcium ricinoleate solution. Maintain the reaction at 75°C for 2 hours.
[0080] (2) Cool to 60°C, add 2 kg of DMF solvent, and then add 1.455 kg of furfurylamine (15.0 mol) and react for 3.5 hours.
[0081] (3) Add 2.685 kg (7.5 mol) of bismaleimide and keep warm at 60°C for 24 hours.
[0082] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA modified castor oil calcium soap stabilizer.
[0083] Example 3
[0084] The hydroxyl content of the barium castor oil raw material was accurately measured, and the hydroxyl value was 144.875 mgkOH / g.
[0085] (1) Purge nitrogen into the reaction vessel to remove air. Take 5 kg of barium ricinoleate (containing about 12.935 mol of hydroxyl groups) and heat it to 150°C. Turn off the nitrogen and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool it to 70-80°C under a nitrogen atmosphere. Add 10 kg of polyurethane-grade solvent toluene and start stirring until the barium ricinoleate is completely dissolved. Control the temperature at 75°C and add 2.251 kg (about 12.935 mol) of TDI-100 dropwise into the calcium ricinoleate solution. Maintain the reaction at 75°C for 2 hours.
[0086] (2) Cool to 60°C, add 2 kg of DMF solvent, and then add 1.255 kg of furfurylamine (12.94 mol) and react for 3.5 hours.
[0087] (3) Add 2.246 kg (6.275 mol) of bismaleimide and keep warm at 60°C for 24 hours.
[0088] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA-modified barium castor oil soap stabilizer.
[0089] Example 4
[0090] The hydroxyl content of the lanthanum ricinoleate raw material was accurately measured, and the hydroxyl value was 154.85 mg kOH / g.
[0091] (1) Purge nitrogen into the reaction vessel to remove air. Take 5 kg (containing about 13.826 mol of hydroxyl groups) of lanthanum ricinoleate and heat it to 150°C. Turn off the nitrogen and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool it to 70-80°C under a nitrogen atmosphere. Add 10 kg of polyurethane-grade solvent toluene and start stirring until the lanthanum ricinoleate is completely dissolved. Control the temperature at 75°C and add 2.41 kg (about 13.85 mol) of TDI-100 dropwise into the lanthanum ricinoleate solution. Maintain the reaction at 75°C for 2 hours.
[0092] (2) Cool to 60°C, add 2 kg of DMF solvent, and then add 1.314 kg of furfurylamine (13.85 mol) and react for 3.5 hours.
[0093] (3) Add 2.479 kg (6.925 mol) of bismaleimide and keep warm at 60°C for 24 hours.
[0094] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA-modified lanthanum ricinoleate soap stabilizer.
[0095] Example 5
[0096] (1) Purge nitrogen into the reaction vessel to remove air. Take 4.5 kg (containing about 13.474 mol of hydroxyl groups) of calcium ricinoleate and 1.5 kg of zinc ricinoleate (containing about 4.318 mol of hydroxyl groups), heat to 150°C, turn off the nitrogen, and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool to 70-80°C under a nitrogen atmosphere. Add 12 kg of polyurethane-grade solvent toluene and start stirring until the ricinoleate soap is completely dissolved. Control the temperature at 75°C. Add 4.448 kg (about 17.792 mol) of molten MDI dropwise to the solution of calcium ricinoleate and zinc ricinoleate mixed soap and maintain the reaction at 75°C for 0.5 hours.
[0097] (2) Cool to 60°C, add 4 kg of DMF solvent, and then add 1.726 kg of furfurylamine (17.792 mol) and react for 3.5 hours.
[0098] (3) Add 3.185 kg (8.896 mol) of bismaleimide and keep warm at 60°C for 24 hours.
[0099] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA modified castor oil calcium zinc co-soluble soap stabilizer.
[0100] Example 6
[0101] (1) Purge nitrogen into the reaction vessel to remove air. Take 4.5 kg (containing about 12.956 mol of hydroxyl groups) of barium ricinoleate and 1.5 kg of zinc ricinoleate (containing about 4.491 mol of hydroxyl groups), heat to 150°C, turn off the nitrogen, and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool to 70-80°C under a nitrogen atmosphere. Add 12 kg of polyurethane-grade solvent toluene and start stirring until the ricinoleate soap is completely dissolved. Control the temperature at 75°C. Add 4.361 kg (about 17.447 mol) of molten MDI dropwise to the solution of calcium and zinc ricinoleate mixed soap and maintain the reaction at 75°C for 0.5 hours.
[0102] (2) Cool to 60°C, add 4 kg of DMF solvent, and then add 1.692 kg of furfurylamine (17.447 mol) and react for 3.5 hours.
[0103] (3) Add 3.12 kg (8.724 mol) of bismaleimide and keep warm at 60°C for 24 hours.
[0104] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA modified castor oil barium zinc co-solution soap stabilizer.
[0105] Example 7
[0106] (1) Purge nitrogen into the reaction vessel to remove air. Take 4.5 kg (containing about 12.443 moles of hydroxyl groups) of lanthanum ricinoleate and 1.5 kg of zinc ricinoleate (containing about 4.491 moles of hydroxyl groups), heat to 150°C, turn off the nitrogen, and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool to 70-80°C under a nitrogen atmosphere. Add 12 kg of polyurethane-grade solvent toluene and start stirring until the ricinoleate soap is completely dissolved. Control the temperature at 75°C. Add 4.234 kg (about 16.943 moles) of molten MDI dropwise to the solution of the lanthanum ricinoleate and zinc ricinoleate mixed soap and maintain the reaction at 75°C for 0.5 hours.
[0107] (2) Cool to 60°C, add 4 kg of DMF solvent, and then add 1.643 kg of furfurylamine (16.943 mol) and react for 3.5 hours.
[0108] (3) Add 3.033 kg (8.472 mol) of bismaleimide and keep warm at 60°C for 24 hours.
[0109] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA-modified castor oil lanthanum zinc co-solution soap stabilizer.
[0110] Example 8
[0111] The hydroxyl content of the hydrogenated zinc ricinoleate raw material was accurately measured, and the hydroxyl value was 160.24 mg kOH / g. The hydroxyl content of the hydrogenated calcium ricinoleate raw material was also accurately measured, and the hydroxyl value was 166.51 mg kOH / g.
[0112] (1) Purge nitrogen into the reaction vessel to remove air. Take 4.5 kg (containing about 13.38 mol of hydroxyl groups) of hydrogenated calcium ricinoleate and 1.5 kg of hydrogenated zinc ricinoleate (containing about 4.292 mol of hydroxyl groups), heat to 150°C, turn off the nitrogen, and evacuate to below 0.67 kPa for 60 minutes to remove excess moisture. Turn off the vacuum and cool to 70-80°C under a nitrogen atmosphere. Add 12 kg of polyurethane-grade solvent toluene and start stirring until the ricinoleic acid soap is completely dissolved. Control the temperature at 75°C. Add 4.418 kg (about 17.672 mol) of molten MDI dropwise to the solution of the calcium and zinc ricinoleate mixed soap and maintain the reaction at 75°C for 0.5 hours.
[0113] (2) Cool to 60°C, add 4 kg of DMF solvent, and then add 1.714 kg of furfurylamine (17.672 mol) and react for 3.5 hours.
[0114] (3) Add 3.163 kg (8.836 mol) of bismaleimide and keep warm at 60°C for 24 hours.
[0115] (4) Heat the reaction solution to above 100°C and turn on the vacuum distillation apparatus to remove the solvent. The solids at the bottom of the vessel are cooled and crushed to obtain DA modified hydrogenated castor oil calcium zinc co-solution soap stabilizer.
[0116] Application Example 1
[0117] I. Crosslinking performance test
[0118] The modified metal soap heat stabilizer prepared in Examples 1-8 and the PVC base formula containing additives were added to a high-speed mixer and mixed at high speed until the plasticizer was completely absorbed and formed a uniform powder. The mixture was then extruded into sheets at 195°C on the plasticizing end using a twin-screw compounding extruder. The sheets were then placed in a special pressing die and pressed into 2mm test pieces at 190°C for later use.
[0119] The basic formulation (parts by weight) for testing the crosslinking performance of PVC containing additives is as follows:
[0120]
[0121] Gel test method: The cross-linking effect is evaluated by testing gel content and tensile strength. After cross-linking, the gel content will increase and the tensile strength of the sample will increase. The device used to measure gel content is a Soxhlet extractor. The specific implementation steps are as follows: (1). Accurately weigh and record about 0.5g of sample sheet, place it in sulfuric acid paper and wrap and seal it. There should be at least 3 samples in each group; (2) Place the sample in a Soxhlet extractor, add tetrahydrofuran and soak for 24 hours, and then heat and reflux at 69°C for 48 hours. (3) Take out the sample and place it in a fume hood to evaporate the solvent for 60 minutes. Finally, place it in a vacuum drying room at 55°C to dry to constant weight, weigh and record; (4) The gel content is expressed as the weight percentage W% remaining in PVC. The specific calculation formula is as follows:
[0122] W% = m2 / (m0-m1) x 100%
[0123] In the formula, m0 is the initial mass, m2 is the remaining mass after Soxhlet extraction, and m1 is the mass of plasticizers and other substances in the sample that are soluble in tetrahydrofuran.
[0124] Tensile strength test method: Use a 2mm specimen and perform the test according to the method specified in GB / T528;
[0125] Testing instrument: FR-104B computerized tensile testing machine
[0126] Equipment manufacturer: Shanghai Farui Instrument Technology Co., Ltd.
[0127] The stretching rate was 500 mm / min, and the sample was a dumbbell-shaped specimen with specific dimensions of 75 mm * 12.5 mm * 4 mm.
[0128] The mass fractions of heat stabilizers added and the test results in each application example and comparative example are shown in Table 1. It can be seen that the tensile strength of the samples using DA-modified calcium zinc castor oil stabilizer is significantly improved, the gel content is greatly increased, and the crosslinking effect is obvious.
[0129] Table 1. Application examples and comparative examples of crosslinking agents, stabilizer formulations, and mechanical property data in crosslinking agent testing.
[0130]
[0131]
[0132] II. Thermal stability performance test:
[0133] The DA-modified metallic soap heat stabilizers prepared in Examples 1-8 were added to the PVC base formulation containing additives in a high-speed mixer and kneaded evenly. The mixture was then plasticized at 160°C for 5 minutes using a two-roll mill, and drawn into test pieces with a thickness of approximately 1 mm for performance testing. The PVC base formulation containing additives, by weight, is as follows:
[0134]
[0135] Test Method: The static thermal stability test method (oven color change method) was adopted, referring to ASTM 2115-67. The test piece was placed on an aluminum sheet and heated at a constant temperature of 180℃ in a thermal aging test chamber. Samples were taken every 10 minutes, and the color change of the test piece was observed to evaluate the thermal stability. The lighter the color change of the test piece, the better the stabilizing effect of the corresponding heat stabilizer. The color of the test piece is expressed numerically, and the corresponding relationship is shown in Table 2 below. The mass fraction of heat stabilizer added in each application example and comparative example is shown in Table 3, and the test data is shown in Table 4.
[0136] Table 2 Standard Grades for Color Change Comparison of Test Pieces
[0137]
[0138]
[0139] Table 3. Formulations of heat stabilizers used in application examples and comparative examples in thermal stability testing.
[0140]
[0141] Table 4 Thermal stability test results
[0142]
[0143] As can be seen from Application Examples 1-7 and Comparative Examples 1-7 in Table 4, the DA-modified ricinoleic acid soap or DA-modified hydrogenated ricinoleic acid soap prepared in Examples 1-8 of this invention has better stabilizing effects than the unmodified ricinoleic acid soap and hydrogenated ricinoleic acid soap. Furthermore, the modified barium soap has better effects than the calcium soap, and the eutectic soap has better effects than the compound soap.
[0144] III. Compression Desorption Test
[0145] Formula A is kneaded until homogeneous and then plasticized at 160°C for 5 minutes on a plasticizer. Formula B, also kneaded until homogeneous, is then plasticized under the same conditions on the same plasticizer. During this process, the red pigment that was pressed out from Formula A and adhered to the roller surface is transferred to Formula B, causing it to turn red. The degree of redness of the plasticized Formula B is compared with that of a standard red plate to determine the degree of separation of the tested stabilizer. The standard red plate is prepared by adding different amounts of red pigment (Permanent Red F4R) to Formula B and then plasticizing. Formulas A and B are shown in Table 5, and the correspondence between the degree of separation (grade) and the red pigment content of the standard red plate is shown in Table 6.
[0146] Table 5. Specific raw materials (parts by mass) for formulations A and B in the pressure precipitation test.
[0147] PVC 100 100 DOP 50 50 Permanent Red F4R 1 / lubricant / 1 Titanium dioxide / 4 Dibutyltin lauryl ester / 2 Heat stabilizer 2 /
[0148] Table 6. Correspondence between the degree of compression and the red pigment content of the standard red plate.
[0149]
[0150] The modified metal soap heat stabilizers prepared in Examples 1-8 were tested and compared using the above-described pressure precipitation method, and the pressure precipitation grades are shown in Table 7 below. It can be seen that the urethane-modified ricinoleic acid soap has significantly improved compatibility with PVC, thus noticeably improving the soap's pressure precipitation properties.
[0151] Table 7. Compression precipitation test results of various heat stabilizers
[0152] DA-modified zinc ricinoleate 1 Zinc ricinoleate 3 DA-modified calcium ricinoleate 1 Calcium ricinoleate 9 DA-modified lanthanum ricinoleate 1 Lanthanum ricinoleate 3 Calcium stearate 10 DA-modified hydrogenated ricinoleate calcium and zinc co-solution soap 1 Hydrogenated castor oil calcium zinc coprecipitate soap 8.
[0153] IV. Blooming Test
[0154] The formula for the spray test is as follows (by weight): 100 parts PVC, 50 parts DOP, 1 part carbon black, and 3 parts of the metal soap to be tested.
[0155] Preparation of comparative test panels: After kneading the ingredients evenly, plasticize them at 160℃ for 5 minutes on a plasticizer, and then press them into 3mm thick test black panels using a flat vulcanizing machine. Place the test black panels in a 0.5% calcium chloride aqueous solution at 60℃ for 72 hours. Compare the whiteness of the test black panel with that of the standard black panel to determine the blooming degree (grade) of the tested stabilizer.
[0156] Standard blackboards are made by adding different amounts of stearic acid to a basic formula (100 parts PVC, 50 parts DOP, 1 part tribasic lead sulfate, and 1 part carbon black). The relationship between blooming degree and stearic acid content of standard blackboards is shown in Table 8.
[0157] The blooming degree of different soap stabilizers was tested and compared as shown in Table 9 below. It can be seen that the urethane-modified zinc ricinoleate soap has significantly improved compatibility with PVC and does not produce blooming.
[0158] Table 8. Correspondence between blooming degree and standard blackboard stearic acid content
[0159]
[0160]
[0161] Table 9. Spraying properties of different soap stabilizers
[0162] Zinc stearate 8 Zinc ricinoleate 7 Zinc hydrogenated ricinoleate 8 DA-modified zinc ricinoleate 0 DA-modified hydrogenated ricinoleate calcium and zinc co-solution soap 0
Claims
1. A zinc-containing metal soap heat stabilizer for PVC, characterized in that, Based on a total mass of 100 parts, the raw material components include the following: 10-85 parts of primary stabilizer; Synergistic stabilizer 15-90 parts; The mass ratio of the primary stabilizer to the synergistic stabilizer is 1:3; The main stabilizer has the structure shown in Formula I: (I) The synergistic stabilizer has the structure shown in Formula II: (II) Wherein, R1 is CH2CH2 or CH=CH, R2 is a diisocyanate residue, R3 is NH or O, M is any one or more of alkaline earth metal elements and rare earth metal elements; n=2, 3 or 4.
2. The zinc-containing metal soap heat stabilizer for PVC according to claim 1, characterized in that, The alkaline earth metal elements include one or more of Mg, Ca, Sr, and Ba; And / or, the rare earth metal elements include one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y; And / or, the diisocyanate residues are derived from any one or more of MDI, TDI, HDI, and PDI.
3. The zinc-containing metal soap heat stabilizer for PVC according to claim 1, characterized in that, The preparation method of the primary stabilizer or synergistic stabilizer includes the following steps: Step 1: Reaction of castor oil soap with diisocyanate yields intermediate A; Step 2: Intermediate A is reacted with furanol or furanylmethylamine to generate intermediate B; Step 3: React intermediate B with bismaleimide to obtain the main stabilizer or synergistic stabilizer; ; When preparing the main stabilizer, the ricinoleic acid soap in step 1 is zinc ricinoleate or hydrogenated zinc ricinoleate; X in the structural formulas of intermediates A and B is Zn; When preparing the synergistic stabilizer, in step 1, the ricinoleic acid soap is any one of ricinoleic acid alkaline earth soap, ricinoleic acid rare earth soap, hydrogenated ricinoleic acid alkaline earth soap, and hydrogenated ricinoleic acid rare earth soap; in the structural formulas of intermediate A and intermediate B, X is M, and M is any one or more of alkaline earth metal elements and rare earth metal elements.
4. The method for preparing a zinc-containing metal soap heat stabilizer for PVC according to any one of claims 1-3, characterized in that, Including the following steps: Step 1: Reaction of castor oil soap with diisocyanate yields intermediate A; Step 2: Intermediate A is reacted with furanol or furanylmethylamine to generate intermediate B; Step 3: React intermediate B with bismaleimide to obtain the main stabilizer or synergistic stabilizer; Step 4: Weigh the main stabilizer and synergistic stabilizer according to the proportions specified in claim 1 to prepare the zinc-containing metal soap heat stabilizer; ; When preparing the main stabilizer, the ricinoleic acid soap in step 1 is zinc ricinoleate or hydrogenated zinc ricinoleate; X in the structural formulas of intermediates A and B is Zn; When preparing the synergistic stabilizer, in step 1, the ricinoleic acid soap is any one of ricinoleic acid alkaline earth soap, ricinoleic acid rare earth soap, hydrogenated ricinoleic acid alkaline earth soap, and hydrogenated ricinoleic acid rare earth soap; in the structural formulas of intermediate A and intermediate B, X is M, and M is any one or more of alkaline earth metal elements and rare earth metal elements.
5. The method for preparing a zinc-containing metal soap heat stabilizer for PVC according to claim 4, characterized in that, Including the following steps: Step 1: Heat the castor oil soap until it melts, remove excess water by vacuuming, add solvent to dissolve it, then add diisocyanate and react at 55-80℃ for 0.5-6 hours. Step 2: Add furanol or furanylmethylamine to the reaction mixture from Step 1, and react at 55-80°C for 2-6 hours. Step 3: Add bismaleimide to the reaction mixture from Step 2, react at 55-80°C for 4-12 hours, remove the solvent from the reaction solution and dry to obtain the main stabilizer or synergistic stabilizer. Step 4: Weigh the main stabilizer and synergistic stabilizer according to the proportions specified in claim 1 to prepare the zinc-containing metal soap heat stabilizer.
6. The method for preparing the zinc-containing metal soap heat stabilizer for PVC according to claim 5, characterized in that, The molar ratio of the diisocyanate to the hydroxyl group of the ricinoleic acid soap is 0.8-1.2:1; And / or, the molar ratio of furanol methanol or furan methylamine to diisocyanate is 0.8-1.2:1; And / or, the molar ratio of the bismaleimide to furanol or furanylmethylamine is 0.45-0.55:1; And / or, the reaction processes in steps 1-3 are all carried out under the protection of an inert gas, which includes one or more of nitrogen and argon; And / or, the solvent includes one or more of toluene, xylene, DMF, DMAC, and DEF.
7. The method for preparing the zinc-containing metal soap heat stabilizer for PVC according to claim 5, characterized in that, In step 1, the ricinoleic acid soap is dissolved by heating. And / or, in step 1, after the castor oil soap is melted, a vacuum is applied to remove excess moisture; And / or, in step 2 or step 3, add reaction solvent.
8. A highly stable PVC material, characterized in that, The product comprises, by weight, 100 parts of PVC matrix and 1-10 parts of the zinc-containing metal soap heat stabilizer as described in any one of claims 1-3.
9. The highly stable PVC material according to claim 8, characterized in that, By weight, including raw materials: 100 parts of PVC matrix; 1-10 parts of the zinc-containing metal soap heat stabilizer; DOP 20-40 copies; 2-6 parts of epoxidized soybean oil; Antioxidant 0.1~0.5 parts; β-Diketone 0.05~0.2; Lubricant 0.05~0.5 parts.
10. The method for preparing the highly stable PVC material according to claim 8 or 9, characterized in that, The process includes the following steps: mechanically blending all raw materials and melt-extruding to obtain the PVC material.
Citation Information
Patent Citations
Oxidized graphene salt-based PVC environment-friendly composite stabilizer and preparation method thereof
CN103571108A
Modified metallic soap heat stabilizer and preparation method and application thereof
CN112010779A
Liquid calcium and zinc heat stabilizer for multiple-effect castor oil-based PVC (polyvinyl chloride) and preparation method and application of liquid calcium and zinc heat stabilizer
CN106750524A
Polyurethane modified asphalt based on DA thermal reversible dynamic covalent bonds and preparation method thereof
CN116285397A